Modelling the spatiotemporal change of urban heat islands and influencing parameters - Ali, Jasim Mohammed (2017)
This study identifies the spatial and temporal change of three types of Urban Heat Island (UHI). The Surface Urban Heat Island (SUHI) and Canopy Urban Heat Island (CUHI) are common UHI phenomena; however, the Radiant Urban Heat Island (RUHI) is proposed as a new type of UHI. Surface temperature, air temperature, and mean radiant temperature are used as indicators to measure the SUHI, CUHI, and RUHI respectively. Visual, statistical and microclimate approaches are carried out to increase the spatial and temporal resolution of the UHI modelling. The modelling approaches employ the integration of remote sensing, GIS, and ground measurements to improve the 2D and 3D representation of the UHI. Furthermore, the influencing parameters on the formation of the three types of UHI are investigated. The research aim is to produce an integrated approach that improves the low spatial or temporal coverage of UHI models in the literature. Moreover, it quantifies the causative parameters on the formation of UHI, and proposes mitigation strategies accordingly. London, Baghdad and Birmingham are the study areas of the SUHI, to test the variability of the size, population, Land Use/Cover (LULC), geometry, microclimate, geography, and level of development. Birmingham is chosen to study the CUHI and RUHI, because of the availability of the required data to model these UHIs. The SUHI is carried out between (2000- 2015) by the Land Surface Temperature (LST) of the thermal bands of Landsat, ASTER, MODIS and other auxiliary data. The CUHI, on the hand, is undertaken for two years (June 2012- June 2014) using high density air temperature measurements (HiTemp data), and the RUHI is simulated based on the mean radiant temperature (Tmrt) for four seasonal days that are part of the HiTemp. The integrated approach of the research employs three indictors (LST, air temperature, and Tmrt) to model the UHI which is unprecedented in the literature. Furthermore, within the use of each indicator there is a novel approach. The LST is acquired for three different cities using thermal bands from 1 m to 1000 m spatial resolution by employing diverse satellite and airborne images for about 15 years. The air temperature is hourly measured for two years by over 100 ground stations to produce high spatial and temporal thermal maps, and some of the ground stations are used to simulate the Tmrt. The Tmrt is used for the first time to model the UHI as a new indictor, which upgrades the 2D UHI using LST and air temperature to 3D UHI simulation. The influencing parameters on the formation of three types of UHI derived from the three indicators are identified, and they include many potential factors not investigated together in the literature. The findings of such topic might be useful for decision-makers when building new cities or modifying the existing ones, even the public can know more about their environment. The results show that, London and Birmingham core area usually work as SUHI during the day and night-time. However, Baghdad city exhibits low LST in the daytime except for high density residential area as well as indusial and commercial units. Similarly, Baghdad city becomes a SUHI in the night-time, and the water bodies have high LST during the cold nights for the three cities. Despite the higher diurnal, daytime and night-time LST of Baghdad compared to London and Birmingham, the London SUHI intensities were higher than those of Baghdad. The temporal change of the average LST and SUHI for Birmingham did not show significant change over the study period just like London; however, they both gave high spatial variability. The diurnal averages of SUHI are 9.41, 11.29, and 7.63 ºC for Baghdad, London, and Birmingham (during 2003-2015) respectively. The CUHI appear daytime and night-time in Birmingham urban and suburban areas throughout the different seasons for 56% of the total hours of two years, to reach 13.53 ºC. The simulation of Tmrt show the presence of daytime Radiant Urban Cool Island (RUCI) in the City Centre of Birmingham, while, the night-time induced the development of RUHI. Various influencing parameters contribute to the different types of UHI. The land cover types and anthropogenic heat are the main contributors to the SUHI. Fourteen controllable and uncontrollable predictors control the CUHI development. On the other hand, the radiation fluxes and shadow patterns direct the RUHI formation. Overall, the spatial and temporal behaviour of UHI varies for the different types of UHI. Each type of UHI is controlled by a set of causative parameters, and these might differ based on the type of UHI as well as where and when it occurs.